Study of the effect of vitamin D supplementation on the clinical, metabolic, and hormonal profile of women with polycystic ovary syndrome in walled city of Delhi - Ajmani, Sangita N.; Singh, Ankita; Mathur, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Polycystic ovary syndrome (PCOS) is a ubiquitous endocrine disorder often associated with vitamin D deficiency, which may contribute to reproductive and metabolic disturbances. This work gauged the influence of vitamin D supplementation on the clinical, metabolic, hormonal, and sonographic profiles of women having PCOS. Methods: A hospital-based case control study initially included 60 women diagnosed with PCOS. The final sample size was 56, as two participants in the case group conceived, one in the control group conceived, and another control participant was lost to follow-up. The remaining 56 women were equally divided into two groups: cases (receiving metformin 500 mg BD for 12 weeks + vitamin D 60,000 IU once weekly for 12 weeks with advice for lifestyle and dietary modification) and controls (receiving metformin 500 mg BD for 12 weeks with advice for lifestyle and dietary modification). Clinical symptoms, menstrual patterns, and metabolic, hormonal, and sonographic parameters were evaluated before and after the intervention. Results: Vitamin D supplementation significantly improved infrequent menses (78.6% to 46.4%, p=0.027) and scanty menses (50% to 21.4%, p=0.048) compared to controls. Weight gain reduced markedly in cases (71.4% to 25%, p=0.0013). Significant reductions were observed in fasting glucose (p=0.001) and postprandial glucose (p=0.022), with high density lipoprotein (HDL) showing a significant rise (p<0.001). Hormonal parameters showed no significant changes. Right ovarian volume decreased modestly (p=0.046). Conclusion: Vitamin D supplementation in PCOS women improved menstrual regularity, weight-related symptoms, glycaemic control, HDL cholesterol, and ovarian morphology, but had limited effects on hormonal parameters.